Implementasi kansei engineering dalam pengembangan kemasan minuman kopi ready to drink - Novi Purnama Sari; Zulkarnain Zulkarnain; Verian Ardi Muzaki; Yuni Dita Meilani (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Currently, the coffee business is becoming a trend in the market. So determining the right packaging design is an important thing to plan. The product development method that has been proven optimal is Kansei engineering. This study compares the results of developing ready-to-drink coffee packaging (cold and hot) with the Kansei engineering method based on consumer emotions. Kansei engineering is a powerfull method that can translate consumer needs into design elements. This method is supported by several multivariate statistical methods and artificial intelligence methods. The results obtained for a cold coffee drink are 25 packaged samples and 30 Kansei words, while 20 samples and 20 Kansei words for a hot coffee drink. The packaging design concepts for a cold coffee drink obtained from Kansei word extraction using the principal component analysis (PCA) method are